1996
DOI: 10.1007/bf02550954
|View full text |Cite
|
Sign up to set email alerts
|

One-session bilateral ureteroscopy: Is it safe in selected patients?

Abstract: The aim of this study was to investigate the possibility to perform bilateral ureteroscopy in one session and to determine the procedure's indications and complication rate. Twenty-two patients underwent bilateral ureteroscopy in one session. Eighteen patients had bilateral lithiasis of the lower ureteral third, three patients had unexplained haematuria and one had unexplained bilateral hydronephrosis. The rigid ureteroscope was used in cases with stones and the flexible one in cases with haematuria and hydron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 6 publications
2
25
0
3
Order By: Relevance
“…No major complications were observed. Our complication rate of 12.9% is comparable with other studies that reported bilateral single-session URS for bilateral stones [5,25,26]. To achieve successful results with low complication rates, good visibility and careful advancement of the ureterorenoscope in the ureter are necessary.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…No major complications were observed. Our complication rate of 12.9% is comparable with other studies that reported bilateral single-session URS for bilateral stones [5,25,26]. To achieve successful results with low complication rates, good visibility and careful advancement of the ureterorenoscope in the ureter are necessary.…”
Section: Discussionsupporting
confidence: 75%
“…They concluded that the risk is proportional to the number of renal units treated. Deliveliotis et al [26] reported that one session of bilateral URS can be performed safely with a stone-free rate of 83.3%. Camilleri et al [5] found an 81% success rate, which was directly related to stone burden and location.…”
Section: Discussionmentioning
confidence: 99%
“…no major complication was observed. They reported that bilateral ureteroscopy in one session can be performed safely in selected patients (1). In contrast, Hollenbeck et al reported that bilateral ureteroscopy carries out an increased risk of postoperative morbidity.…”
Section: Commentsmentioning
confidence: 99%
“…With the recent development of small-caliber ureteroscopes and with the advances in intracorporeal lithotripsy devices, it is now possible to perform bilateral single-session URSL in adults, and ureteric stones may be fragmented successfully. The procedure may reduce costs and the need for a second anesthetic procedure (1,2). There are few reports in the literature about single-session URSL for the management of bilateral ureteral stones.…”
Section: Original Article Introductionmentioning
confidence: 99%
See 1 more Smart Citation